2007
DOI: 10.1007/s10534-007-9125-4
|View full text |Cite
|
Sign up to set email alerts
|

Features of ceruloplasmin in the cerebrospinal fluid of Alzheimer’s disease patients

Abstract: The level of the apo-form of the copper enzyme ceruloplasmin (CP) is an established peripheral marker in diseases associated with copper imbalance. In view of the proposal that disturbances of copper homeostasis may contribute to neurodegeneration associated with Alzheimer's disease (AD), the present work investigates, by Western blot and non-reducing SDS-PAGE followed by activity staining, the features of CP protein, and the copper/CP relationship in cerebrospinal fluid (CSF) and serum of AD patients. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 28 publications
2
40
1
Order By: Relevance
“…7d) confirmed that phagocytosis was unimpeded by CSF and that purified CP and APP, which are largely excluded from CSF, remained inhibitory to phagocytosis in the CSF medium. Interestingly, all three inhibitory glycoproteins identified in this study have also been implicated in neurodegeneration, particularly Alzheimer disease (37,38). Our identification of CP, SAP, and APP as inhibitory proteins for phagocytosis of apoptotic cells mediated by P2X7 or other scavenger receptors may provide new insights into the pathogenesis of neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 58%
“…7d) confirmed that phagocytosis was unimpeded by CSF and that purified CP and APP, which are largely excluded from CSF, remained inhibitory to phagocytosis in the CSF medium. Interestingly, all three inhibitory glycoproteins identified in this study have also been implicated in neurodegeneration, particularly Alzheimer disease (37,38). Our identification of CP, SAP, and APP as inhibitory proteins for phagocytosis of apoptotic cells mediated by P2X7 or other scavenger receptors may provide new insights into the pathogenesis of neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 58%
“…The spots at high molecular weight (135-115 kDa) of the fully denatured protein that we show in this study may represent a pool of the two forms, as we have recently shown in a dedicated study, revealing a conspicuous amount of apo-ceruloplasmin in the CSF of AD patients. 20 The evidence of low-molecular-weight fragments of ceruloplasmin in AD samples suggests that at least a portion of this protein is present in its apoform in general circulation, and indicates that an impairment in the incorporation of copper into the protein may occur in AD during ceruloplasmin biosynthesis. In fact, the six integral copper atoms are incorporated into ceruloplasmin during its biosynthesis through the copper-transporting ATPase ATP7B in the secretory compartment of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In particular, our recent biochemical studies demonstrated that a discrete concentration increase of copper occurs in AD which exceeds the amount of ceruloplasmin, 15 and that a considerable amount of inactive ceruloplasmin can be detected in the cerebrospinal fluid of AD patients. 20 Since ceruloplasmin is the main copper transporter in general circulation, we aimed in the present work at studying the qualitative changes occurring in the ceruloplasmin present in the serum of AD patients, explored by means of a two dimensional polyacrylamide gel electrophoresis (2-D PAGE) approach, to detect possible protein modifications that can be considered explanatory of 'free' copper deregulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesised that the increased "free" copper found in AD was due to a defect in copper incorporation into ceruloplasmin. This hypothesis was supported by: 1) the increased levels of serum apoceruloplasmin derived by the failure of copper binding into ceruloplasmin during its biosynthesis in the liver; 2) liver dysfunction due to "free" copper disturbance of hepatocytes; 3) evidence of the move of "free" copper from the serum to the CSF, overcoming BBB, and of "free" copper interaction with CSF markers of AD [52][53][54][55][56][57].…”
Section: Free Copper Ionmentioning
confidence: 99%
“…85% -95% of the serum copper is tightly bound to ceruloplasmin while the resting "free" copper is bound to albumin, alpha 2 macroglobulin, and low-molecularweight compounds such as peptides and amino acids. The difference between the two copper pools is that the "free" copper overcomes BBB [52,53]. Moreover, in AD patients "free" copper is increased in CSF [54] and in brain parenchyma.…”
Section: Free Copper Ionmentioning
confidence: 99%